Hemoglobin HbA1c and Glucose Blood Levels in Diabetic Patients - Tahirović, Ismet; Mahovac, Enesa; Dizdar, Muamer; Toromanović, Jasmin; Mahmutović, Omer; Lepara, Zahid; Ajanović, Atifa (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Diabetes mellitus (DM) is defined as an absolute or relative lack of insulin, or a state of chronic hyperglycemia. Hemoglobin A1c (HbA1c) is a minor Hb form, produced in vivo by post-translational glycosylation. In the last 30 years, in biochemical laboratory practice, HbA1c became a "gold standard" for clinical monitoring of DM. The aim of this study was to determine the glucose and HbA1c levels in DM suffering patients at “Zavidovići” Health Center in different time periods,and estimate glucoregulation. The levels of HbA1c and glucose were measured in 100 patients with 3-month time period. The results were analyzed by appropriate statistical methods, to determine whether there are statistically significant differences between the two measurements. A spectrophotometric method was used to determine the level of HbA1c, whileglucose was determined using an enzymatic-colorimetric method on biochemical analyzer. It was found that in 61 of the total number of subjects, the levels of HbA1c and glucose were significantly reduced (p***<0.001) three months after the first measurement, which leads to the conclusion that their glucoregulation have improved. In the remaining 39 subjects the levels of HbA1c and glucose were significantly increased (p*<0.05) in the same time period, which leads to the conclusion that their glucoregulation worsened.